2020
DOI: 10.1088/1361-6463/abbb04
|View full text |Cite
|
Sign up to set email alerts
|

High-performance solid-state photon-enhanced thermionic emission solar energy converters with graded bandgap window-layer

Abstract: To realize a high-performance solid-state photon-enhanced thermionic emission (SPETE) solar energy converter, in this study, a graded bandgap window layer is therefore adopted, throughout which the bandgap gradation is generated via the variation of Al composition in the A l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this way, an excessive effort has been made to design and produce state-of-the-art photovoltaic devices to convert this cheap and abundant energy to other applicable resources such as electricity. [3][4][5][6][7][8] In a common way, manipulation of the materials and their combination in different layers of the solar cell devices, especially in electron transport layer (ETL), has resulted in great upshots. [9][10][11] For instance, Ye and coworkers recently designed a bilayer ETL consisting of two tin oxide nanoparticle layers doped with different amounts of ammonium chloride to tune the band level at the corresponding interface, leading to reduced charge recombination, improved electron transfer, and lower voltage loss.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, an excessive effort has been made to design and produce state-of-the-art photovoltaic devices to convert this cheap and abundant energy to other applicable resources such as electricity. [3][4][5][6][7][8] In a common way, manipulation of the materials and their combination in different layers of the solar cell devices, especially in electron transport layer (ETL), has resulted in great upshots. [9][10][11] For instance, Ye and coworkers recently designed a bilayer ETL consisting of two tin oxide nanoparticle layers doped with different amounts of ammonium chloride to tune the band level at the corresponding interface, leading to reduced charge recombination, improved electron transfer, and lower voltage loss.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 The Model 17 with three Cs atoms, respectively, located at T Si1 , B Si2 0 , H 1 sites achieves the lowest work function (0.92 eV), which is extremely approaching to the work function of P-doped diamond films (0.9 eV). 12 Based on the results of Yang et al, 2 the maximum conversion efficiency of PETE devices with anode material of 0.92 eV can reach 30%. These results inspirit us to further explore the feasibility of 3C-SiC material as the anode material candidate of PETE devices.…”
Section: Multiple Cs Atoms Adsorptionmentioning
confidence: 98%
“…The PETE solar converters own a vacuum-gap parallel-plate structure, splitting by a semiconductor cathode, a vacuum gap and a semiconductor or metal anode. 2,3 The working mechanism of PETE devices can be described as a photoelectric emission process. The cathode absorbs solar light from a solar concentrator and excites photoelectrons in the conduction band.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the selection of cathode materials, previous studies have shown that III-V semiconductors have good PETE properties but are concentrated on GaAs-based materials [14][15][16][17]. Both GaN and InN have been applied to PETE converter cathodes, while cathodes based on InGaN ternary compounds have not yet been attempted [7,18].…”
Section: Introductionmentioning
confidence: 99%